2004
DOI: 10.1055/s-2004-834830
|View full text |Cite
|
Sign up to set email alerts
|

Dual Catalyst Control in the Chiral Diamine-Dipeptide-Catalyzed Asymmetric Michael Addition

Abstract: By example of conjugate addition of 2-nitropropane to 2-cyclohexen-1-one, it is shown that the combination of H-Leu-His-OH and (1R,2R)-(+)-1,2-diphenylethylenediamine as co-catalysts in a suitable ratio can lead to a new catalytic system for the C-C bond formation reactions. Although neither co-catalyst is sufficiently effective independently in terms of yield or enantioselectivity, their combination results in a drastic increase in yields (up to 86%) and absolute selectivities (up to 91% ee).The recent contri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(25 citation statements)
references
References 1 publication
1
23
0
1
Order By: Relevance
“…[13] These results clearly evince that catalytic activity and directing effects are, in this case, the result of the self-assembled catalysts instead of synergistic effects. [14] Moreover, this conclusion is also supported by NMR spectroscopy [13] of the l-proline and QD-1 mixture. The scope of this approach was then evaluated, under the optimized conditions, with various ketone, aldehyde, and nitroalkene substrates.…”
Section: Tanmay Mandal and Cong-gui Zhao*supporting
confidence: 54%
“…[13] These results clearly evince that catalytic activity and directing effects are, in this case, the result of the self-assembled catalysts instead of synergistic effects. [14] Moreover, this conclusion is also supported by NMR spectroscopy [13] of the l-proline and QD-1 mixture. The scope of this approach was then evaluated, under the optimized conditions, with various ketone, aldehyde, and nitroalkene substrates.…”
Section: Tanmay Mandal and Cong-gui Zhao*supporting
confidence: 54%
“…In order to further improve the stereoselectivity of the reaction catalyzed by bicyclic amine 2, it was decided to explore a multiple catalysis strategy, [26][27][28][29][30][31][32][33][34][35] by combining catalytic agents, rather than designing new catalysts. Three chiral acids (mandelic, tartaric and camphor sulfonic acid) available in both enantiomeric forms were selected as chiral additives in the Michael addition reaction with (1S,4S)-2-tosyl-2,5-diazabicyclo[2.2.1]heptane as the main catalyst.…”
Section: Resultsmentioning
confidence: 99%
“…[32] The same reaction was also studied by Tsogoeva´s group using the dipeptide H-Leu-His-OH in conjunction with a chiral diamine. [33] In all cases, the authors reported a synergic effect between the two units with respect to the individual chiral catalysts.…”
Section: Introductionmentioning
confidence: 97%
“…Using the conjugate addition of 2-nitropropane to cyclohex-2-en-1-one as an example, we further showed, [10] for the first time, that the combination of the dipeptide H-LeuHis-OH and (1R,2R)-(+)-1,2-diphenylethylenediamine as co-catalysts produced a new catalytic system for C-C bondformation reactions (Scheme 1). Although neither co-catalyst was sufficiently effective independently in terms of yield or enantioselectivity, their combination resulted in a drastic increase in yields (up to 86 %) and selectivities (up to 91 % ee), indicating the possibility of synergistic effects.…”
Section: Conjugate Additions Of Nitro Alkanes To Cycloalkenonesmentioning
confidence: 95%